Blanking die process for production product / Marwan Hasan and Kamarul Baharin Mansor - Hasan, Marwan; Mansor, Kamarul Baharin (Faculty of Mechanical Engineering, 1996)
In blanking or piercing die, the word “die' has been defined as : (a) a complete production tool, the purpose of which is to produce piece part consistently to a required specification, and (b) the female part of a complete die. To produce a desired product or piece part upon the material being worked ( the stock material) a male member ( the punch ) of a complete die mates or act in conjunction with the female die…